Comparative Study Between 2nd and 3rd Class Football Referees InYo -Yo test Results - محسن علي نصيف (College of Physical Education and Sport Sciences, 2020)
The aim of the research is to compare the results of 2nd class football referees with 3rd class football referees in physical fitness test Yo - Yo test. In addition to that the researcher aimed at finding the differences in distances covered in yo - yo tests. the subjects were (15) 2nd class football referee and (15) 3rd class football referees. The researcher concluded that there are weaknesses in speed stamina especially in 3rd class football referees.